Harm, Then Good? How Work Meaningfulness Emerges from Doing Harm - Robertson, Kirsten; Hannah, David; Lautsch, Brenda (Journal of Management Studies, 2024)
AbstractMeaningful work has been identified as an important antecedent of an array of positive outcomes for both workers and their employers. However, many work roles involve harming others, an experience that has previously been linked to negative outcomes such as dissatisfaction and burnout. How does meaningfulness emerge when one's work includes such challenging circumstances? Drawing on interviews and observations in the veterinary industry, we elucidate new theory about the relationship between harm‐doing and the experience of meaningful work. Workers' interpretations of the worthiness of the harm, as well as the types of actions they take to remediate it, influence whether their involvement in harm‐doing episodes undermines or heightens their sense of meaningfulness. We further detail how dimensions of harm‐doing episodes shape opportunities for remediation, as well as whether the episodes ‘stick’ in workers' memories and hence figure into their ongoing, holistic accounts of work meaningfulness. Based on these findings, we introduce a novel ‘work‐bounded, worker‐centric’ view of meaningfulness that incorporates both the nature of work and workers' interpretations of it. Our research has implications for the work meaningfulness and workplace harm literatures, as well as for the many individuals whose work involves doing harm.